The Role of Control Environment in Strengthening Internal Control and Preventing Fraud - Hanif, Aisha; Dina Dwi Oktaviarini; Nur Ravita Hanun (Universitas Indo Global Mandiri, 2025)
Financial information is very important for companies because it can be used for decision making and to attract investors. However, pressure to achieve financial targets, opportunities and rationalization from individuals often encourage individuals in companies to manipulate financial reports. The success of an internal control system in an organization is greatly influenced by the quality of a solid control environment, which does not only depend on the implementation of formal policies and procedures, but is also influenced by individual aspects and values ​​upheld in the organization. This study aims to explore the effectiveness of the internal control environment in detecting and preventing fraud in companies. This study is expected to provide significant contributions to the development of more effective internal control policies that can be widely implemented, as well as provide practical guidance for companies in building an environment that prevents fraud and strengthens corporate governance. This study uses a qualitative approach with data collection techniques through observation, documentation and interviews. The data analysis method used in this study is thematic analysis, which involves the stages of data reduction, data presentation, and drawing conclusions. The findings of this study illustrate that the effectiveness of internal control depends on a strong control environment, supported by policies, individual factors, and organizational values. The integration of spiritual values ​​strengthens integrity, transparency, and compliance. The integration of spiritual values ​​into the control environment contributes significantly to the effectiveness of an organization's internal control system. Keywords: control environment, internal control, fraud